TiO(2) Nanotube Arrays: Fabricated by Soft–Hard Template and the Grain Size Dependence of Field Emission Performance - Yang, Xuxin (Nanoscale Res Lett, 2017)
Highly ordered TiO(2) nanotube (TNT) arrays were successfully synthesized by the combination of soft and hard templates. In the fabrication of them, anodic aluminum oxide membranes act as the hard template while the self-assembly of polystyrene-block-poly(ethylene oxide) (PS-b-PEO) complexed with titanium-tetraisopropoxide (TTIP, the precursor of TiO(2)) provides the soft template to control the grain size of TiO(2) nanotubes. Our results indicate that the field emission (FE) performance depends crucially on the grain size of the calcinated TiO(2) which is dominated by the PS-b-PEO and its blending ratio with TTIP. The optimized sample (with the TTIP/PEO ratio of 3.87) exhibits excellent FE performances involving both a low turn-on field of 3.3 V/um and a high current density of 7.6 mA/cm(2) at 12.7 V/μm. The enhanced FE properties can be attributed to the low effective work function (1.2 eV) resulted from the smaller grain size of TiO(2).